Appropriateness of orthodontic referrals: self-perceived and normative treatment needs of patients referred for orthodontic consultation - Chew MT, Aw AKL. (Blackwell Synergy, 2002)
The aims of this prospective study were to evaluate the selfperceived and normative orthodontic treatment needs of children referred for orthodontic consultation and to determine the proportion of children who were inappropriately referred.